Programa de audiencias públicas y su relación con la satisfacción ciudadana en la ciudad de Iquitos año 2024 - Flores Valdivia, Victor Antonio (2025)
The purpose of the public hearing program of the Comptroller General of the Republic is to promote transparency, citizen participation and social control over public management. But the little importance given to citizen control in public management can result in an increase in corruption, administrative inefficiency, loss of confidence in institutions, which is why the objective of the research is to identify how the relationship between the public hearing program and citizen satisfaction in the city of Iquitos in 2024, with a quantitative observational approach with a non-experimental correlational level. The Public Hearings Program in the city of Iquitos demonstrates a positive and significant relationship with citizen satisfaction, highlighting that both the previous actions, the development of the hearings and the issuance of results directly impact the positive perception of citizens. Previous actions, well planned and disseminated, generate greater satisfaction, while the development of audiences and the issuance of results reinforce transparency and trust in the program. However, areas for improvement are identified in the monitoring of citizen alerts and in the socialization of the results, which suggests the need to strengthen these aspects to maximize the impact of the program and achieve greater citizen satisfaction.